Strategi Pengembangan Lembaga Pendidikan Melalui Analisis SWOT: Suatu Tinjauan Teoritis, Integratif, dan Adaptif - Shelty D. M. Sumual; Joulanda A. M. Rawis; Jeffry S. J. Lengkong; Irithca J. Tengker; Nathaniel Pali (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study discusses the implementation of SWOT analysis as a strategic tool in education management to improve the quality and effectiveness of educational institutions. The main focus of the study is to evaluate the effectiveness, challenges, and best practices of the implementation of SWOT in the context of educational institutions in Indonesia. Through the literature study method, data is collected from various literature sources such as scientific journals, policy documents, and research reports. The results of the study show that SWOT analysis is able to provide a comprehensive overview of the internal (strengths and weaknesses) and external (opportunities and threats) conditions of the institution, thus making it easier to formulate strategies based on real conditions. SWOT has been proven to encourage more adaptive, participatory, and data-driven strategic planning, as well as strengthen stakeholder involvement in the decision-making process. Nonetheless, the successful implementation of SWOT is highly dependent on data quality, managerial capacity, and the sustainability of follow-up from the analysis results. Challenges that often arise are subjectivity in assessment, lack of technical training, and limitations in integrating SWOT into the institution's long-term plan. This study contributes to strengthening the strategic management practice of education in Indonesia, as well as opening up space for further research on the integration of SWOT with other management models such as the Balanced Scorecard and quantitative analysis based on strategic matrices.